Peran Bahasa Indonesia sebagai Bahasa persatuan di era globalisasi - Andreas Riki Daniel Sihombing; Aswin Sianturi; Fasca Kristiani Butar-Butar; Muhammad Surip (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This research aims to explore the role of Indonesian in a unifying context in the era of globalization, using a literature review method. In this era of globalization, Indonesian, as the national language and language of the unity of the Indonesian nation, has a crucial role in uniting people with diverse ethnicities and cultures. This role is increasingly important in the era of globalization, where many people now use foreign languages ​​or slang in daily communication. There is a lot of use of slang in everyday language. The large number of uses of slang in everyday conversations does not eliminate the use of Indonesian, but the meaning and use of good, polite and courteous Indonesian in everyday life becomes blurred. Indonesian is not only a means of communication, but also a means of unifying and strengthening national identity. The conclusion of this research is that Indonesian has an irreplaceable role in uniting the nation. Mastery of Indonesian helps people to become effective communicators, able to convey ideas clearly and understand the various nuances of communication. Therefore, the role of Indonesian, especially in this era of globalization, is very important to ensure that people have a solid foundation in communicating in local and global contexts.